Effect Of Butterfly Hug Therapy On Anxiety In Pre-Operative Patients Scheduled In The Room Imam Bonjol Kindergarten Hospital. Iii Dr. Reksodiwiryo Padang YEAR 2025 - Siska Luniza; Vania Aresti Yendrial; Hidayatul Rahmi; Syalvia Oresti (Jurnal Riset Multidisiplin Edukasi, 2026)
Patients who are about to undergo surgery often experience increased anxiety due to fear of surgical procedures, anesthesia, and possible complications. This anxiety can cause physiological and psychological changes, such as increased heart rate, blood pressure, and respiratory rate. One of the non-pharmacological interventions that can be used to reduce anxiety is Butterfly Hug therapy. This study aims to determine the effect of Butterfly Hug therapy on the anxiety levels of pre-operative patients at RK III DR. Reksodiwiryo Padang in 2025. This study employs a pre-experimental design with a one-group pretest-posttest approach. A sample of 24 pre-operative patients was selected using a purposive sampling technique. The Butterfly Hug intervention was given for 30 minutes before surgery. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) questionnaire before and after the intervention. Data analysis was carried out using the Wilcoxon test. The average anxiety score of pre-operative patients before the intervention was 26.83, which decreased to 21.92 after the intervention, showing a reduction of 18.30%. The results of the Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating that there is a significant effect of Butterfly Hug therapy on reducing anxiety. This therapy can be used as one of the nursing self-help interventions to reduce anxiety before surgery. Researchers are further advised to explore other relaxation techniques that can be applied as alternative non-pharmacological interventions to address pre-operative patient anxiety.